2022
DOI: 10.3390/vaccines10020205
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Hesitancy among Parents and Its Association with the Uptake of Measles Vaccine in Urban Settings in Khartoum State, Sudan

Abstract: Vaccine uptake is one of the indicators that has been used to guide immunization programs. This study aimed to evaluate whether measles vaccine uptake is predicted by measles vaccine hesitancy. A community-based cross-sectional study was conducted in urban districts in Khartoum state in February 2019. Measles vaccine uptake among children was measured as either fully vaccinated or partially/not vaccinated. The Parent Attitudes about Childhood Vaccines (PACV) scale was used to measure measles vaccine hesitancy.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Patterns of increasing pro-poor inequality in child immunization across some LMICs have been reported in the literature before [ 14 , 16 ]. The emergence of vaccine hesitancy, which is usually observed in more economically developed countries [ 59 , 60 ], could explain this phenomenon [ 61 ]. Various factors may influence vaccine hesitancy, such as parents’ perception of the risks and benefits of child immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of increasing pro-poor inequality in child immunization across some LMICs have been reported in the literature before [ 14 , 16 ]. The emergence of vaccine hesitancy, which is usually observed in more economically developed countries [ 59 , 60 ], could explain this phenomenon [ 61 ]. Various factors may influence vaccine hesitancy, such as parents’ perception of the risks and benefits of child immunization.…”
Section: Discussionmentioning
confidence: 99%
“…explain this phenomenon [61]. Various factors may influence vaccine hesitancy, such as parents' perception of the risks and benefits of child immunization.…”
Section: Plos Medicinementioning
confidence: 99%
“…This study is part of a large research project about measles vaccine hesitancy in Sudan [ 21 , 22 ]. The sample size was calculated for the whole research using a power analysis for the association between measles vaccine hesitancy and the measles vaccination status (outcome), which showed that at least 386 participants were needed to yield an 80% power to detect an odds ratio of 1.7 at alpha level (5%).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in Sudan showed the existence of measles vaccine hesitancy is attributed to different drivers including vaccination access-related issues, such as the parental perception that measles vaccination services are unavailable and inaccessible [ 7 , 21 ]. Additionally, a study found that the uptake of the measles vaccine among children is predicted by their parental hesitancy toward the measles vaccine [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[20] Previous studies in Sudan showed the existence of measles vaccine hesitancy is attributed to different drivers including vaccination access-related issues such as the parental perception that measles vaccination services are unavailable and inaccessible [7,21]. Additionally, a study found that the uptake of the measles vaccine among children is predicted by their parental hesitancy toward the measles vaccine [22].…”
Section: Introductionmentioning
confidence: 99%